Pengaruh Ketinggian Pemangkasan Dengan Mesin Potrum Srt-03 Terhadap Torsi Pemangkasan Rumput Bermuda (Cynodon dactylon) Tiff Way 146 - I Putu Surya Wirawan; I Nengah Suastawa; Nizar Nasrullah (Jurnal Keteknikan Pertanian, 2008)
Rotary mower is one of mowing tools commonly used to maintain lawn or turfgrass. Mowing height and mowing torque are important factors that should be taken into account in sustaining grass quality and designing a rotary mower. The study was addressed to recognize the influence ofmowing height to required mowing torque. The mowing torque was measured at mowing height of 2, 3 and 4 em. Measurement of mowing torque in the field was done by using a specially designed turfgrass mowing apparatus that representing rotary mowing mechanism. The apparatus was equipped with torque measurement system. The average measured torque was used to calculate the power requirement of mowing. The needs of maximum and minimum mowing torque to mow turfgrass for all mowing height were 0,68 Nm and 0,05 Nm. The average of mowing torque were 0,51 Nm, 0,24 Nm, and 0,08 Nm, at mowing height of 2, 3 and 4 em respectively. The maximum and minimum power that required for all mowing height was 196,4 watt and 14,4 watt.Keywords: mowing, rotary mower, turfgrass.Diterirna: 4 Februari 2008; Disefujui: 2 Juni 2008